2018
DOI: 10.1177/0022219418815646
|View full text |Cite
|
Sign up to set email alerts
|

Examining Reading Comprehension Profiles of Grade 5 Monolinguals and English Language Learners Through the Lexical Quality Hypothesis Lens

Abstract: This study set out to compare patterns of relationships among phonological skills, orthographic skills, semantic knowledge, listening comprehension, and reading comprehension in English as a first language (EL1) and English language learners (ELL) students and to test the applicability of the lexical quality hypothesis framework. Participants included 94 EL1 and 178 ELL Grade 5 students from diverse home-language backgrounds. Latent profile analyses conducted separately for ELLs and EL1s provided support for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 77 publications
5
29
0
1
Order By: Relevance
“…Our findings suggest that poor comprehenders experience difficulties in both oral language skills such as vocabulary breadth and listening comprehension, and metalinguistic skills such as morphological awareness. Previous research reported lower performance on listening comprehension, vocabulary and morphological awareness in ELL poor comprehenders when they were compared to ELL good comprehenders (Geva & Massey-Garrison, 2013;Lesaux & Kieffer, 2010;O'Connor et al, 2019;Zhang & Shulley, 2017). Our findings extend this body of research by showing that ELL poor comprehenders also perform worse on these skills than average comprehenders.…”
Section: The Reading Profile Of Ell Poor Comprehenderssupporting
confidence: 81%
See 2 more Smart Citations
“…Our findings suggest that poor comprehenders experience difficulties in both oral language skills such as vocabulary breadth and listening comprehension, and metalinguistic skills such as morphological awareness. Previous research reported lower performance on listening comprehension, vocabulary and morphological awareness in ELL poor comprehenders when they were compared to ELL good comprehenders (Geva & Massey-Garrison, 2013;Lesaux & Kieffer, 2010;O'Connor et al, 2019;Zhang & Shulley, 2017). Our findings extend this body of research by showing that ELL poor comprehenders also perform worse on these skills than average comprehenders.…”
Section: The Reading Profile Of Ell Poor Comprehenderssupporting
confidence: 81%
“…This is expected because ELLs have reduced exposure to English. Preliminary evidence suggests that ELL poor comprehenders demonstrate persistent difficulties in oral language, metalinguistic, and cognitive skills such as vocabulary, morphological awareness, syntactic awareness, listening comprehension, and working memory as well as higher-level skills such as inference and reading strategies (e.g., (Farnia & Geva, 2019;Geva & Massey-Garrison, 2013); Kieffer & Vukovic, 2012; (Lesaux & Kieffer, 2010;Lesaux, Koda, et al, 2006a;Lesaux, Lipka, & Siegel, 2006b;Lipka & Siegel, 2012;O'Connor et al, 2019;Zhang & Shulley, 2017)). It is important to note that most of these skills are reliant on and predicted by vocabulary knowledge which ELLs lack (Cain, Oakhill, & Lemmon, 2004b).…”
Section: Reading Comprehension Difficulties In Ell Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Listening comprehension has also been shown to play a role in reading comprehension in L2 readers (for a meta‐analysis, see Jeon & Yamashita, 2014) and specifically in EFL readers (e.g., Li & Kirby, 2014; O’Connor, Geva, & Koh, 2019). However, research on the contribution of listening comprehension to EFL lexical processing has been limited (see Jean & Geva, 2009).…”
Section: Reader‐specific Predictors Of Efl Word‐reading Skillmentioning
confidence: 99%
“…We have used a cutoff criteria of below the 30th percentile which might include L2 at-risk English readers who were not at-risk. Recent studies have used other identification methods such as growth curve models (S. S. Yeung, 2018) or latent profile analysis (O'Connor et al, 2019) to accurately identify at-risk ESL children. Future research should adopt these identification methods and examine the effects of DMG interventions.…”
Section: Limitations and Future Workmentioning
confidence: 99%